X+Y+Z=36

Simple and best practice solution for X+Y+Z=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+Y+Z=36 equation:


Simplifying
X + Y + Z = 36

Solving
X + Y + Z = 36

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1Y' to each side of the equation.
X + Y + -1Y + Z = 36 + -1Y

Combine like terms: Y + -1Y = 0
X + 0 + Z = 36 + -1Y
X + Z = 36 + -1Y

Add '-1Z' to each side of the equation.
X + Z + -1Z = 36 + -1Y + -1Z

Combine like terms: Z + -1Z = 0
X + 0 = 36 + -1Y + -1Z
X = 36 + -1Y + -1Z

Simplifying
X = 36 + -1Y + -1Z

See similar equations:

| x+9=4(5+2) | | 0.4y-6.7+y-0.3-26y= | | 0.4y-6.7+-0.3-26y= | | 6.4c=0.8 | | 6cos^2(x)+7sin(x)-1=0 | | 6x+10+3sinx=0 | | 7p-14=7(p-2) | | 15/250=1/x | | 10-5h=5(-h+2) | | 5x+24=8x+27 | | 15/250=x/15 | | 10c=5(2c+13) | | -15w-9=3(-5w-3) | | 20+r=7r-11r-10 | | -15+m=8(-3m+20) | | (1/4x)-(3/x)=-9/8 | | 15y+5y-9=20y-9 | | 6y+2t= | | 5-4-5z=-5z+1 | | 2(11u+12)=18u-20 | | -19+6g+14=6g+14 | | 11+8-15s=19-15s | | (-3m-6)(7m+1)= | | 18b-9b+18=18+9b | | 340+4x^2-56x=25+x^2+6x | | 17-6v+18=-6v-19 | | 1/2-6/7 | | 1/2x-1/7=-3/5 | | 53.30/8.20 | | 3x/450=140 | | X+.05x=10 | | 3x^2-50x+315=0 |

Equations solver categories